The Amsterdam Tapestry Producer Alexander Baert (1660–1719) and his Workshop: New Findings. (2nd January 2019) - Beerens, Rudy Jos
Abstract : Drawing on archival material relating to the Amsterdam tapestry producer Alexander Baert, much of it previously unpublished, this research note marks a departure from the prevailing, undersocialised, approach to tapestry production and trade in the Northern Netherlands. Data explored here for the first time show that, before emigrating from Oudenaarde, Baert was an active member of a rich network of tapestry entrepreneurs, but that 'push factors' such as legal and commercial problems along with 'pull factors' such as certain benefits and freedoms prompted his decision to move to the Republic. While earlier studies describe his activities there as an isolated process, it becomes clear that the entrepreneur and his descendants preserved enduring business ties in the Southern Netherlands. These networks furnished Baert with the infrastructure that enabled him to import tapestries from Antwerp, Brussels and Oudenaarde and to purchase Flemish cartoons cheaply.